The intersectional importance of race/ethnicity, disability, and age in flu vaccine uptake for U.S. adults - Rebecca D. Breaux; Ronica N. Rooks (Elsevier, 2022)
Improving vaccination rates among marginalized populations is an important priority among public policy makers and healthcare providers in the United States of America (U.S.). Racial/ethnic minorities have a long history of reduced vaccination rates relative to white Americans (Khan, Hall, Tanner, & Marlow, 2018), while people with disabilities (PWD) have varied rates of vaccine use (Diab & Johnston, 2004; O'Neill, Newall, Antolovich, Lima, & Danchin, 2019). Yet, little is known about vaccine use among individuals who belong to both groups. This study examines the intersectional effects of race/ethnicity and disability on flu vaccine use. We used the 2015-2018 National Health Interview Survey to examine the odds of flu vaccine use by race/ethnicity, disability, and their interaction among adults aged 18+ in the U.S. non-institutionalized, civilian population stratified by age groups. For each unit increase in disability scores, we found a significant race-by-disability interaction for young black adults (18-39 years) who had higher odds of getting the flu vaccine compared to white adults in the same age group. A significant interaction occurred for middle-aged Hispanic vs. white adults (40-64 years) who had higher odds of getting the flu vaccine as their disability scores increased. Black vs. white adults were less likely to get the flu vaccine across all age groups irrespective of disability and other covariates, while results were more mixed among other racial/ethnic groups. Additionally, people with disabilities had higher odds of flu vaccination. Further, race/ethnicity had a moderating effect on the relationship between disability and flu vaccination and an interaction effect occurred between disability and certain racial/ethnic groups when stratified by age.